Mannitol in Critical Care and Surgery Over 50+ Years: A Systematic Review of Randomized Controlled Trials and Complications With Meta-Analysis. Issue 3 (July 2019) - Zhang, Weiliang; Neal, Jonathan; Lin, Liang; Dai, Feng; Hersey, Denise P.; McDonagh, David L.; Su, Fan; Meng, Lingzhong
Abstract : Objective: Despite clinical use spanning 50+ years, questions remain concerning the optimal use of mannitol. The published reviews with meta-analysis frequently focused on mannitol's effects on a specific physiological aspect such as intracranial pressure (ICP) in sometimes heterogeneous patient populations. A comprehensive review of mannitol's effects, as well as side effects, is needed. Methods: The databases Medline (OvidSP), Embase (OvidSP), and NLM PubMed were systematically searched for randomized controlled trials (RCTs) comparing mannitol to a control therapy in either the critical care or perioperative setting. Meta-analysis was performed when feasible to examine mannitol's effects on outcomes, including ICP, cerebral perfusion pressure, mean arterial pressure (MAP), brain relaxation, fluid intake, urine output, and serum sodium. Systematic literature search was also performed to understand mannitol-related complications. Results: In total 55 RCTs were identified and 7 meta-analyses were performed. In traumatic brain injury, mannitol did not lead to significantly different MAP (SMD [95% confidence interval (CI)] =−3.3 [−7.9, 1.3] mm Hg; P =0.16) but caused significantly different serum sodium concentrations (SMD [95% CI]=−8.0 [−11.0, −4.9] mmol/L; P <0.00001) compared with hypertonic saline. In elective craniotomy, mannitol was less likely to lead to satisfactory brain relaxation (RR [95% CI]=0.89 [0.81, 0.98]; P =0.02), but was associated with increased fluid intake (SMD [95% CI]=0.67 [0.21, 1.13] L; P =0.004), increased urine output (SMD [95% CI]=485 [211, 759] mL; P =0.0005), decreased serum sodium concentration (SMD [95% CI]=−6.2 [−9.6, −2.9] mmol/L; P =0.0002), and a slightly higher MAP (SMD [95% CI]=3.3 [0.08, 6.5] mm Hg; P =0.04) compared with hypertonic saline. Mannitol could lead to complications in different organ systems, most often including hyponatremia, hyperkalemia, and acute kidney injury. These complications appeared dose dependent and had no long-term consequences. Conclusions: Mannitol is effective in accomplishing short-term clinical goals, although hypertonic saline is associated with improved brain relaxation during craniotomy. Mannitol has a favorable safety profile although it can cause electrolyte abnormality and renal impairment. More research is needed to determine its impacts on long-term outcomes. Abstract : Supplemental Digital Content is available in the text.